The microwave absorbing properties of ZnO/Fe3O4/paraffin composites in low frequency band. (23rd February 2018) - Yin, Pengfei; Deng, Yu; Zhang, Limin; Huang, Juan; Li, Huayao; Li, Youhongyu; Qi, Yali; Tao, Yu
Abstract: ZnO/Fe3 O4 /paraffin composites with good microwave absorption performance in low frequency band were prepared by physical blending technology. The morphology, phase structures, frequency-dependent electromagnetic and microwave absorbing properties of the composites were investigated. The results showed that the addition content of ZnO can adjust the microwave absorbing properties i.e. the position, intensity, and absorption bandwidth of composites, and the synergetic consequence of dielectric loss and magnetic loss is the main microwave absorption mechanism of the composites. The bandwidths with RL below −10 dB over different frequency ranges were obtained in the low frequency range of 0.5 ∼ 3 GHz at a thickness of 5 mm, e.g. 0.93 GHz from 1.59 to 2.52 GHz and 0.85 GHz from 1.26 to 2.11 GHz corresponding to the mass ratios of ZnO and Fe3 O4 are 1:2 and 1:4, respectively. Thus, such absorbers can be applied as effective microwave absorbers in low frequency range of 0.5 ∼ 3 GHz.